Understanding effects of the algorithm visualized with AR techniques - Lima, Lázaro V. O. (2021)
We create analogies to understand and visualize complex concepts. Such approach, based on analogies are presentation of software, is also effective when it concerns software comprehension. Many visualization techniques for data structures have been developed in 2D and 3D to improve the visual representation of large structures. A common challenge faced by developers that want to implement these techniques is to increase the amount of information to be displayed in each node seeking a balance between quantity and visibility. To overcome these challenges, this article presents a visualization technique using Augmented Reality to display hierarchical structures and understand the effects of the algorithm in data structures. The visualization system based on AR, proposed and discussed along the paper, allows the user to interact and navigate through the structure, enabling him to explore information in depth.